Novel high-strength polymer anchor rod and preparation method thereof

Through the chemical reaction and blending and modification treatment of modified ultra-high molecular polyethylene and isophthalicide, combined with the molding and sintering treatment, the fiberglass anchor rod has been solved, and the material compatibility, processing difficulty, toughness and insufficient stability under complex conditions of coal mines is low, and the anchor rod performance is achieved with high strength, durability and stable.

CN119661979APending Publication Date: 2025-03-21XUZHOU HUAZE ENG MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411750550.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing fiberglass anchor rods have problems such as low material compatibility, high processing difficulty, low toughness and insufficient stability in application scenarios such as roadways in complex conditions of coal mines and rapid excavation.

Method used

Modified ultra-high molecular polyethylene and isophthalide are used to chemically react to form a film-like adhesion layer to improve the adhesion between fibers, and optimize the compatibility and processing properties of the material by blending the modified ultra-high molecular polyethylene and adding polyethylene glycol and crosslinking agent. Use molding and sintering to improve the mechanical properties and wear resistance of the material.

Benefits of technology

It significantly improves the tensile strength and flame retardant properties of the material, improves compatibility and toughness, improves stability and wear resistance, and is suitable for tunnel environments under complex conditions of coal mines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661979A_ABST
    Figure CN119661979A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of anchor rods, in particular to a novel high-strength polymer anchor rod and a preparation method of the novel high-strength polymer anchor rod. 5 to 25 parts of modified ultra-high molecular weight polyethylene; 1 to 5 parts of m-phenyl diester bis; 1-4 parts of a lubricant; and 0.5-3 parts of a coupling agent. The modified ultra-high molecular weight polyethylene and the m-phenyl diester are subjected to chemical reaction, so that the tensile strength of the material is remarkably improved. In the process of preparing the modified ultra-high molecular weight polyethylene, the high-density polyethylene and the liquid crystal high-molecular polymer are added, so that the shear viscosity of the system is reduced, and the compatibility and toughness of the material are improved; the polyethylene glycol is added, so that the toughness of the material is increased, the fluidity of the material is improved, and the processability is further improved; and the added 2, 5-dimethyl-2, 5-di-tert-butylperoxy-3-acetylene is used as a cross-linking agent to carry out cross-linking reaction on the ultra-high molecular weight polyethylene, so that the wear resistance of the ultra-high molecular weight polyethylene is improved by more than two times, and the stability is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anchor rods, and specifically refers to a novel high-strength polymer anchor rod and a preparation method thereof. Background Art

[0002] FRP anchor rods, as a new type of steel bar material that integrates glass fiber, resin and other auxiliary materials and is processed at high temperature, have shown broad application prospects in many fields such as construction, transportation, and ships. Although FRP anchor rods have many advantages such as low density, high strength, corrosion resistance, non-conductivity and insulation, they still have many performance deficiencies in application scenarios such as complex conditions in coal mines and rapid excavation.

[0003] UHMWPE (Ultra-High Molecular Weight Polyethylene) is considered an ideal material for improving the performance of anchor bolts due to its excellent properties such as wear resistance, high strength and chemical stability. However, the application of UHMWPE in anchor bolts also faces some technical challenges. For example, how to ensure the compatibility between UHMWPE and the anchor bolt matrix, how to optimize the processing technology, and how to evaluate the impact of UHMWPE on the overall performance of the anchor bolt. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a new type of high-strength polymer anchor rod and a preparation method thereof, in order to solve the problems of low material compatibility, great processing difficulty, low toughness and insufficient stability in the prior art.

[0005] The first aspect of the present application provides a novel high-strength polymer anchor rod, which comprises the following components by weight: fiberglass matrix: 80-130 parts; modified ultra-high molecular polyethylene: 5-25 parts; isophthalic acid bis(ester): 1-5 parts; lubricant: 1-4 parts; coupling agent: 0.5-3 parts.

[0006] Optionally, the anchor rod comprises the following components by weight: glass fiber reinforced plastic matrix: 90-120 parts; modified ultra-high molecular polyethylene: 10-20 parts; isophthalic acid bis(ester): 2-4 parts; lubricant: 2-3 parts; coupling agent: 1-2 parts.

[0007] Optionally, the fiberglass matrix is ​​composed of epoxy resin and glass fiber in a weight ratio of 5:1.

[0008] Optionally, the lubricant is one of paraffin or stearic acid.

[0009] Optionally, the coupling agent is silane KH-570.

[0010] Optionally, the modified ultra-high molecular polyethylene comprises the following components by weight: ultra-high molecular polyethylene: 40-50 parts; high-density polyethylene: 30-40 parts; liquid crystal high molecular polymer: 1-10 parts; polyethylene glycol: 1-2 parts; and cross-linking agent: 1-5 parts.

[0011] Optionally, the cross-linking agent is 2,5-dimethyl-2,5-di-tert-butylperoxy-3-ethyne.

[0012] Optionally, the liquid crystal polymer is one of a polyaromatic amide liquid crystal polymer and a polyaromatic heterocyclic liquid crystal polymer.

[0013] The second aspect of the present application provides a method for preparing a novel high-strength polymer anchor rod, the method comprising:

[0014] Step 1: preparing a glass fiber reinforced plastic matrix and modified ultra-high molecular weight polyethylene respectively, wherein ultra-high molecular weight polyethylene, high-density polyethylene and liquid crystal polymer are blended and modified, and polyethylene glycol and a cross-linking agent are added in sequence to obtain modified ultra-high molecular weight polyethylene;

[0015] Step 2: chemically reacting the prepared modified ultra-high molecular weight polyethylene with isophthalate;

[0016] Step 3: fully mix the product prepared in step 2, the glass fiber reinforced plastic matrix, the lubricant and the coupling agent, and perform compression molding using a compression molding process;

[0017] Step 4: The formed product is sequentially subjected to resin dipping, sintering, air cooling and cutting according to a braiding process with a preset number of strands to obtain a new type of high-strength polymer anchor rod.

[0018] Optionally, the sintering temperature is 200° C.-250° C., and the sintering time is 2-4 hours.

[0019] Therefore, this application has at least the following beneficial effects:

[0020] (1) By chemically reacting the modified ultra-high molecular weight polyethylene with isophthalate, a film-like adhesion layer can be formed on the surface of the modified ultra-high molecular weight polyethylene, and an adhesion effect can be produced between the fibers. During the stretching process, these film-like adhesions and the adhesion between the fibers can effectively share part of the load, thereby significantly improving the tensile strength of the material. In addition, the coating effect of isophthalate on the surface of the material also gives it excellent flame retardant properties;

[0021] (2) In the process of preparing modified ultra-high molecular weight polyethylene, high-density polyethylene and liquid crystal polymers are added to reduce the shear viscosity of the system, improve the compatibility and toughness of the material, thereby improving the processing fluidity of ultra-high molecular weight polyethylene, and at the same time, showing the characteristics of high strength and high modulus;

[0022] (3) In the process of preparing modified ultra-high molecular weight polyethylene, the addition of polyethylene glycol effectively acts on the amorphous region of ultra-high molecular weight polyethylene, reduces the entanglement density of the polymer, increases the toughness of the material, and improves its fluidity, thereby improving the processing performance;

[0023] (4) In the process of preparing modified ultra-high molecular weight polyethylene, 2,5-dimethyl-2,5-di-tert-butylperoxy-3-acetylene was added as a cross-linking agent to perform a cross-linking reaction on the ultra-high molecular weight polyethylene, thereby increasing its wear resistance by more than two times and significantly improving its stability;

[0024] (5) The preparation method of the novel high-strength polymer anchor provided by the present invention uses a compression molding process and performs compression molding in a temperature range of 200°C to 250°C. During the compression process, constant pressure and temperature must be maintained to ensure that the material is uniform and dense. The finished product after molding needs to be sintered. The sintering process is carried out at a high temperature to fully extend and arrange the molecular chains, improve the mechanical properties and wear resistance of the material, and set a braiding process with different numbers of strands to make it have higher performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0026] Figure 1 A flow chart of a method for preparing a novel high-strength polymer anchor provided in an embodiment of the present invention.

[0027] Figure 2 A DSC schematic diagram of a novel high-strength polymer anchor provided by an embodiment of the present invention;

[0028] Figure 3 This is a scanning electron microscope image of the new high-strength polymer anchor provided in Example 4 of the present invention. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] In the examples of the present invention, if there is no special description of raw materials or processing techniques, it is indicated that they are all conventional commercially available raw materials or conventional processing techniques in the art.

[0031] A novel high-strength polymer anchor rod and its preparation method according to an embodiment of the present application are described below with reference to the accompanying drawings. In response to the problem of insufficient anchor rod performance mentioned in the above background technology, the present application provides a novel high-strength polymer anchor rod, which can form a film-like attachment on the surface of the modified ultra-high molecular polyethylene and produce an attachment effect between the fibers by chemically reacting the modified ultra-high molecular polyethylene with isophthalate. During the stretching process, these film-like attachments and attachments between the fibers can effectively share part of the load, thereby significantly improving the tensile strength of the material. In addition, the coating effect of isophthalic acid diester on the surface of the material also gives it excellent flame retardant properties; in the process of preparing modified ultra-high molecular weight polyethylene, the addition of high-density polyethylene and liquid crystal polymer reduces the shear viscosity of the system, improves the compatibility and toughness of the material, thereby improving the processing fluidity of ultra-high molecular weight polyethylene, and at the same time, shows the characteristics of high strength and high modulus; the addition of polyethylene glycol effectively acts on the amorphous region of ultra-high molecular weight polyethylene, reduces the entanglement density of the polymer, not only increases the toughness of the material, but also improves its fluidity, thereby improving the processing performance; the addition of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-acetylene as a cross-linking agent, cross-linking reaction of ultra-high molecular weight polyethylene is carried out, which increases its wear resistance by more than two times and significantly improves stability; using the compression molding process, the compression molding is carried out in the temperature range of 200℃ to 250℃, and the pressure and temperature must be maintained constant during the pressing process to ensure that the material is uniform and dense. The finished product after molding needs to be sintered. The sintering process is carried out at high temperature to fully extend and arrange the molecular chains, thereby improving the mechanical properties and wear resistance of the material. Thereby, the problems of low material compatibility, great processing difficulty, low toughness and insufficient stability in the prior art are solved.

[0032] Example 1

[0033] The present application provides a novel high-strength polymer anchor rod, which comprises the following components by weight: glass fiber reinforced plastic matrix: 90 parts; modified ultra-high molecular polyethylene: 10 parts; isophthalic acid bis(ester): 2 parts; lubricant: 2 parts; coupling agent: 1 part.

[0034] The fiberglass matrix is ​​composed of epoxy resin and glass fiber in a weight ratio of 5:1.

[0035] Wherein, the lubricant is paraffin.

[0036] Wherein, the coupling agent is silane KH-570.

[0037] The modified ultra-high molecular weight polyethylene comprises the following components by weight: ultra-high molecular weight polyethylene: 40 parts; high-density polyethylene: 30 parts; liquid crystal polymer: 2 parts; polyethylene glycol: 1 part; and cross-linking agent: 1 part.

[0038] Wherein, the cross-linking agent is 2,5-dimethyl-2,5-di-tert-butylperoxy-3-acetylene.

[0039] The liquid crystal polymer is one of polyaromatic amide liquid crystal polymer and polyaromatic heterocyclic liquid crystal polymer.

[0040] The second aspect of the present application provides a method for preparing a novel high-strength polymer anchor rod, such as Figure 1 As shown, the preparation method comprises:

[0041] In step S101, a fiberglass matrix and modified ultrahigh molecular weight polyethylene are prepared respectively, wherein ultrahigh molecular weight polyethylene, high density polyethylene and liquid crystal polymer are blended and modified, and polyethylene glycol and a cross-linking agent are added in sequence to obtain modified ultrahigh molecular weight polyethylene.

[0042] It can be understood that the embodiment of the present application successfully prepared a modified ultra-high molecular weight polyethylene material with excellent comprehensive performance by blending modified ultra-high molecular weight polyethylene with high-density polyethylene and liquid crystal polymer, and adding polyethylene glycol as a plasticizer and cross-linking agent for treatment, which not only improved the processing fluidity and mechanical properties, but also enhanced the heat resistance and chemical stability.

[0043] In step S102, the prepared modified ultra-high molecular weight polyethylene is chemically reacted with isophthalate.

[0044] It can be understood that the embodiments of the present application significantly enhance the surface adhesion and inter-fiber bonding force of the material by allowing the modified ultra-high molecular weight polyethylene to undergo a chemical reaction with isophthalate, while also improving its flame retardancy, mechanical properties, and heat resistance.

[0045] In step S103, the product prepared in step 2, the FRP matrix, the lubricant and the coupling agent are fully mixed and pressed into shape using a compression molding process.

[0046] It is understandable that the embodiment of the present application makes full use of the performance advantages of both by combining the reaction product of modified ultra-high molecular polyethylene and isophthalate and the glass fiber reinforced plastic matrix to form a complementary effect. The glass fiber reinforced plastic matrix provides good strength and rigidity, and the product after the reaction may bring excellent wear resistance, chemical corrosion resistance and flame retardancy. The addition of lubricant helps to reduce the friction and resistance of the mixture during the molding process, making the pressing process smoother, and also helps to improve the surface smoothness and quality of the final product. Coupling agent can enhance the interfacial bonding between different materials and improve the overall performance of composite material.

[0047] In step S104, the formed product is sequentially subjected to resin dipping, sintering, air cooling and cutting according to a braiding process with a preset number of strands to obtain a novel high-strength polymer anchor rod.

[0048] Among them, the sintering temperature is 200°C, the sintering time is 2h, and the preset number of strands can be determined according to actual needs.

[0049] It can be understood that the embodiment of the present application uses a braiding process with a preset number of strands to perform resin dipping, sintering, air cooling and cutting in sequence to prepare a high-strength, durable and stable anchor rod. The anchor rod has excellent performance, is suitable for the complex conditions of coal mine tunnels, and effectively improves the support effect and service life.

[0050] Example 2

[0051] The present application provides a novel high-strength polymer anchor rod, which comprises the following components by weight: glass fiber reinforced plastic matrix: 100 parts; modified ultra-high molecular polyethylene: 12 parts; isophthalic acid bis(isophthalate): 2.5 parts; lubricant: 2.2 parts; coupling agent: 1.2 parts.

[0052] The fiberglass matrix is ​​composed of epoxy resin and glass fiber in a weight ratio of 5:1.

[0053] Wherein, the lubricant is stearic acid.

[0054] Wherein, the coupling agent is silane KH-570.

[0055] The modified ultra-high molecular weight polyethylene comprises the following components by weight: ultra-high molecular weight polyethylene: 42 parts; high-density polyethylene: 32 parts; liquid crystal polymer: 4 parts; polyethylene glycol: 1.2 parts; and cross-linking agent: 2 parts.

[0056] Wherein, the cross-linking agent is 2,5-dimethyl-2,5-di-tert-butylperoxy-3-acetylene.

[0057] The liquid crystal polymer is one of polyaromatic amide liquid crystal polymer and polyaromatic heterocyclic liquid crystal polymer.

[0058] The second aspect of the present application provides a method for preparing a novel high-strength polymer anchor rod, such as Figure 1 As shown, the preparation method comprises:

[0059] In step S101, a fiberglass matrix and modified ultrahigh molecular weight polyethylene are prepared respectively, wherein ultrahigh molecular weight polyethylene, high density polyethylene and liquid crystal polymer are blended and modified, and polyethylene glycol and a cross-linking agent are added in sequence to obtain modified ultrahigh molecular weight polyethylene.

[0060] It can be understood that the embodiment of the present application successfully prepared a modified ultra-high molecular weight polyethylene material with excellent comprehensive performance by blending modified ultra-high molecular weight polyethylene with high-density polyethylene and liquid crystal polymer, and adding polyethylene glycol as a plasticizer and cross-linking agent for treatment, which not only improved the processing fluidity and mechanical properties, but also enhanced the heat resistance and chemical stability.

[0061] In step S102, the prepared modified ultra-high molecular weight polyethylene is chemically reacted with isophthalate.

[0062] It can be understood that the embodiments of the present application significantly enhance the surface adhesion and inter-fiber bonding force of the material by allowing the modified ultra-high molecular weight polyethylene to undergo a chemical reaction with isophthalate, while also improving its flame retardancy, mechanical properties, and heat resistance.

[0063] In step S103, the product prepared in step 2, the FRP matrix, the lubricant and the coupling agent are fully mixed and pressed into shape using a compression molding process.

[0064] It is understandable that the embodiment of the present application makes full use of the performance advantages of both by combining the reaction product of modified ultra-high molecular polyethylene and isophthalate and the glass fiber reinforced plastic matrix to form a complementary effect. The glass fiber reinforced plastic matrix provides good strength and rigidity, and the product after the reaction may bring excellent wear resistance, chemical corrosion resistance and flame retardancy. The addition of lubricant helps to reduce the friction and resistance of the mixture during the molding process, making the pressing process smoother, and also helps to improve the surface smoothness and quality of the final product. Coupling agent can enhance the interfacial bonding between different materials and improve the overall performance of composite material.

[0065] In step S104, the formed product is sequentially subjected to resin dipping, sintering, air cooling and cutting according to a braiding process with a preset number of strands to obtain a novel high-strength polymer anchor rod.

[0066] Among them, the sintering temperature is 200°C, the sintering time is 2h, and the preset number of strands can be determined according to actual needs.

[0067] It can be understood that the embodiment of the present application uses a braiding process with a preset number of strands to perform resin dipping, sintering, air cooling and cutting in sequence to prepare a high-strength, durable and stable anchor rod. The anchor rod has excellent performance, is suitable for the complex conditions of coal mine tunnels, and effectively improves the support effect and service life.

[0068] Example 3

[0069] The present application provides a novel high-strength polymer anchor rod, which comprises the following components by weight: glass fiber reinforced plastic matrix: 110 parts; modified ultra-high molecular polyethylene: 15 parts; isophthalic acid bis(isophthalate): 3 parts; lubricant: 2.5 parts; coupling agent: 1.5 parts.

[0070] The fiberglass matrix is ​​composed of epoxy resin and glass fiber in a weight ratio of 5:1.

[0071] Wherein, the lubricant is paraffin.

[0072] Wherein, the coupling agent is silane KH-570.

[0073] The modified ultra-high molecular weight polyethylene comprises the following components by weight: ultra-high molecular weight polyethylene: 45 parts; high-density polyethylene: 35 parts; liquid crystal polymer: 6 parts; polyethylene glycol: 1.5 parts; and cross-linking agent: 3 parts.

[0074] Wherein, the cross-linking agent is 2,5-dimethyl-2,5-di-tert-butylperoxy-3-acetylene.

[0075] The liquid crystal polymer is one of polyaromatic amide liquid crystal polymer and polyaromatic heterocyclic liquid crystal polymer.

[0076] The second aspect of the present application provides a method for preparing a novel high-strength polymer anchor rod, such as Figure 1 As shown, the preparation method comprises:

[0077] In step S101, a fiberglass matrix and modified ultrahigh molecular weight polyethylene are prepared respectively, wherein ultrahigh molecular weight polyethylene, high density polyethylene and liquid crystal polymer are blended and modified, and polyethylene glycol and a cross-linking agent are added in sequence to obtain modified ultrahigh molecular weight polyethylene.

[0078] It can be understood that the embodiment of the present application successfully prepared a modified ultra-high molecular weight polyethylene material with excellent comprehensive performance by blending modified ultra-high molecular weight polyethylene with high-density polyethylene and liquid crystal polymer, and adding polyethylene glycol as a plasticizer and cross-linking agent for treatment, which not only improved the processing fluidity and mechanical properties, but also enhanced the heat resistance and chemical stability.

[0079] In step S102, the prepared modified ultra-high molecular weight polyethylene is chemically reacted with isophthalate.

[0080] It can be understood that the embodiments of the present application significantly enhance the surface adhesion and inter-fiber bonding force of the material by allowing the modified ultra-high molecular weight polyethylene to undergo a chemical reaction with isophthalate, while also improving its flame retardancy, mechanical properties, and heat resistance.

[0081] In step S103, the product prepared in step 2, the FRP matrix, the lubricant and the coupling agent are fully mixed and pressed into shape using a compression molding process.

[0082] It is understandable that the embodiment of the present application makes full use of the performance advantages of both by combining the reaction product of modified ultra-high molecular polyethylene and isophthalate and the glass fiber reinforced plastic matrix to form a complementary effect. The glass fiber reinforced plastic matrix provides good strength and rigidity, and the product after the reaction may bring excellent wear resistance, chemical corrosion resistance and flame retardancy. The addition of lubricant helps to reduce the friction and resistance of the mixture during the molding process, making the pressing process smoother, and also helps to improve the surface smoothness and quality of the final product. Coupling agent can enhance the interfacial bonding between different materials and improve the overall performance of composite material.

[0083] In step S104, the formed product is sequentially subjected to resin dipping, sintering, air cooling and cutting according to a braiding process with a preset number of strands to obtain a novel high-strength polymer anchor rod.

[0084] Among them, the sintering temperature is 200°C, the sintering time is 2h, and the preset number of strands can be determined according to actual needs.

[0085] It can be understood that the embodiment of the present application uses a braiding process with a preset number of strands to perform resin dipping, sintering, air cooling and cutting in sequence to prepare a high-strength, durable and stable anchor rod. The anchor rod has excellent performance, is suitable for the complex conditions of coal mine tunnels, and effectively improves the support effect and service life.

[0086] Example 4

[0087] The present application provides a novel high-strength polymer anchor rod, which comprises the following components by weight: glass fiber reinforced plastic matrix: 110 parts; modified ultra-high molecular polyethylene: 18 parts; isophthalic acid bis(isophthalate): 3.5 parts; lubricant: 2.8 parts; coupling agent: 1.8 parts.

[0088] The fiberglass matrix is ​​composed of epoxy resin and glass fiber in a weight ratio of 5:1.

[0089] Wherein, the lubricant is stearic acid.

[0090] Wherein, the coupling agent is silane KH-570.

[0091] The modified ultra-high molecular polyethylene comprises the following components by weight: ultra-high molecular polyethylene: 40-50 parts; high-density polyethylene: 38 parts; liquid crystal polymer: 8 parts; polyethylene glycol: 1.8 parts; and cross-linking agent: 4 parts.

[0092] Wherein, the cross-linking agent is 2,5-dimethyl-2,5-di-tert-butylperoxy-3-acetylene.

[0093] The liquid crystal polymer is one of polyaromatic amide liquid crystal polymer and polyaromatic heterocyclic liquid crystal polymer.

[0094] The second aspect of the present application provides a method for preparing a novel high-strength polymer anchor rod, such as Figure 1 As shown, the preparation method comprises:

[0095] In step S101, a fiberglass matrix and modified ultrahigh molecular weight polyethylene are prepared respectively, wherein ultrahigh molecular weight polyethylene, high density polyethylene and liquid crystal polymer are blended and modified, and polyethylene glycol and a cross-linking agent are added in sequence to obtain modified ultrahigh molecular weight polyethylene.

[0096] It can be understood that the embodiment of the present application successfully prepared a modified ultra-high molecular weight polyethylene material with excellent comprehensive performance by blending modified ultra-high molecular weight polyethylene with high-density polyethylene and liquid crystal polymer, and adding polyethylene glycol as a plasticizer and cross-linking agent for treatment, which not only improved the processing fluidity and mechanical properties, but also enhanced the heat resistance and chemical stability.

[0097] In step S102, the prepared modified ultra-high molecular weight polyethylene is chemically reacted with isophthalate.

[0098] It can be understood that the embodiments of the present application significantly enhance the surface adhesion and inter-fiber bonding force of the material by allowing the modified ultra-high molecular weight polyethylene to undergo a chemical reaction with isophthalate, while also improving its flame retardancy, mechanical properties, and heat resistance.

[0099] In step S103, the product prepared in step 2, the FRP matrix, the lubricant and the coupling agent are fully mixed and pressed into shape using a compression molding process.

[0100] It is understandable that the embodiment of the present application makes full use of the performance advantages of both by combining the reaction product of modified ultra-high molecular polyethylene and isophthalate and the glass fiber reinforced plastic matrix to form a complementary effect. The glass fiber reinforced plastic matrix provides good strength and rigidity, and the product after the reaction may bring excellent wear resistance, chemical corrosion resistance and flame retardancy. The addition of lubricant helps to reduce the friction and resistance of the mixture during the molding process, making the pressing process smoother, and also helps to improve the surface smoothness and quality of the final product. Coupling agent can enhance the interfacial bonding between different materials and improve the overall performance of composite material.

[0101] In step S104, the formed product is sequentially subjected to resin dipping, sintering, air cooling and cutting according to a braiding process with a preset number of strands to obtain a novel high-strength polymer anchor rod.

[0102] Among them, the sintering temperature is 200°C, the sintering time is 2h, and the preset number of strands can be determined according to actual needs.

[0103] It can be understood that the embodiment of the present application uses a braiding process with a preset number of strands to perform resin dipping, sintering, air cooling and cutting in sequence to prepare a high-strength, durable and stable anchor rod. The anchor rod has excellent performance, is suitable for the complex conditions of coal mine tunnels, and effectively improves the support effect and service life.

[0104] Example 5

[0105] The present application provides a novel high-strength polymer anchor rod, which comprises the following components by weight: glass fiber reinforced plastic matrix: 120 parts; modified ultra-high molecular polyethylene: 20 parts; isophthalic acid bis(isophthalate): 4 parts; lubricant: 3 parts; coupling agent: 2 parts.

[0106] The fiberglass matrix is ​​composed of epoxy resin and glass fiber in a weight ratio of 5:1.

[0107] Wherein, the lubricant is paraffin.

[0108] Wherein, the coupling agent is silane KH-570.

[0109] The modified ultra-high molecular weight polyethylene comprises the following components by weight: ultra-high molecular weight polyethylene: 50 parts; high-density polyethylene: 40 parts; liquid crystal polymer: 10 parts; polyethylene glycol: 2 parts; and cross-linking agent: 5 parts.

[0110] Wherein, the cross-linking agent is 2,5-dimethyl-2,5-di-tert-butylperoxy-3-acetylene.

[0111] The liquid crystal polymer is one of polyaromatic amide liquid crystal polymer and polyaromatic heterocyclic liquid crystal polymer.

[0112] The second aspect of the present application provides a method for preparing a novel high-strength polymer anchor rod, such as Figure 1 As shown, the preparation method comprises:

[0113] In step S101, a fiberglass matrix and modified ultrahigh molecular weight polyethylene are prepared respectively, wherein ultrahigh molecular weight polyethylene, high density polyethylene and liquid crystal polymer are blended and modified, and polyethylene glycol and a cross-linking agent are added in sequence to obtain modified ultrahigh molecular weight polyethylene.

[0114] It can be understood that the embodiment of the present application successfully prepared a modified ultra-high molecular weight polyethylene material with excellent comprehensive performance by blending modified ultra-high molecular weight polyethylene with high-density polyethylene and liquid crystal polymer, and adding polyethylene glycol as a plasticizer and cross-linking agent for treatment, which not only improved the processing fluidity and mechanical properties, but also enhanced the heat resistance and chemical stability.

[0115] In step S102, the prepared modified ultra-high molecular weight polyethylene is chemically reacted with isophthalate.

[0116] It can be understood that the embodiments of the present application significantly enhance the surface adhesion and inter-fiber bonding force of the material by allowing the modified ultra-high molecular weight polyethylene to undergo a chemical reaction with isophthalate, while also improving its flame retardancy, mechanical properties, and heat resistance.

[0117] In step S103, the product prepared in step 2, the FRP matrix, the lubricant and the coupling agent are fully mixed and pressed into shape using a compression molding process.

[0118] It is understandable that the embodiment of the present application makes full use of the performance advantages of both by combining the reaction product of modified ultra-high molecular polyethylene and isophthalate and the glass fiber reinforced plastic matrix to form a complementary effect. The glass fiber reinforced plastic matrix provides good strength and rigidity, and the product after the reaction may bring excellent wear resistance, chemical corrosion resistance and flame retardancy. The addition of lubricant helps to reduce the friction and resistance of the mixture during the molding process, making the pressing process smoother, and also helps to improve the surface smoothness and quality of the final product. Coupling agent can enhance the interfacial bonding between different materials and improve the overall performance of composite material.

[0119] In step S104, the formed product is sequentially subjected to resin dipping, sintering, air cooling and cutting according to a braiding process with a preset number of strands to obtain a novel high-strength polymer anchor rod.

[0120] Among them, the sintering temperature is 200°C, the sintering time is 2h, and the preset number of strands can be determined according to actual needs.

[0121] It can be understood that the embodiment of the present application uses a braiding process with a preset number of strands to perform resin dipping, sintering, air cooling and cutting in sequence to prepare a high-strength, durable and stable anchor rod. The anchor rod has excellent performance, is suitable for the complex conditions of coal mine tunnels, and effectively improves the support effect and service life.

[0122] Comparative Example 1

[0123] This comparative example provides a new type of high-strength polymer anchor rod and its preparation method, which is different from Example 1 only in that the components do not contain high-density polyethylene and liquid crystal polymer, and the reduced amount of high-density polyethylene and liquid crystal polymer is distributed to ultra-high molecular polyethylene. The remaining components and component contents are the same as those in Example 1.

[0124] Comparative Example 2

[0125] This comparative example provides a novel high-strength polymer anchor rod and a preparation method thereof, which differs from Example 1 only in that polyethylene glycol is not included in the components, and the reduced amount of polyethylene glycol is distributed to the ultra-high molecular polyethylene, and the remaining components and component contents are the same as those in Example 1.

[0126] Comparative Example 3

[0127] This comparative example provides a new type of high-strength polymer anchor rod and its preparation method, which is different from Example 1 only in that the components do not contain high-density polyethylene, liquid crystal polymer and polyethylene glycol, and the reduced amount of high-density polyethylene, liquid crystal polymer and polyethylene glycol is distributed to ultra-high molecular polyethylene, and the remaining components and component contents are the same as in Example 1.

[0128] Performance Testing

[0129] The tensile strength, elongation and wear rate of the novel high-strength polymer anchor prepared in Examples 1-5 and Comparative Examples 1-3 were tested respectively. The performance tests are shown in Table 1 below.

[0130] Table 1 Performance test of high strength glass fiber reinforced plastic anchor

[0131] serial number Tensile strength / Mpa Elongation / % Wear rate / % Example 1 27.6 39.5 6.3 Example 2 28.7 40.1 4.5 Example 3 29.5 40.7 2.9 Example 4 30.8 41.6 1.4 Example 5 29.9 40.9 3.6 Comparative Example 1 20.1 36.9 11.1 Comparative Example 2 26.8 31.2 7.8 Comparative Example 3 18.2 30.1 12.6

[0132] like Figure 2 , Figure 3 As shown in Table 1, the new high-strength polymer anchor rod in the embodiment of the present invention has excellent properties such as high tensile strength, high elongation, low wear rate, etc., has low processing difficulty, and can be mass-produced. At the same time, during the production process, it can be made into a solid structure or a hollow structure, thereby reducing costs while meeting performance requirements.

[0133] Using a new type of high-strength polymer anchor provided by the present invention, the tensile strength, elongation and wear rate of Example 4 are the best, among which the tensile strength reaches 30.8Mpa, the elongation reaches 41.6%, and the wear rate reaches 1.4%. Therefore, the toughness of the material is significantly improved, and it has the characteristics of long-term stability. It can be seen that the introduced material needs to be within a certain amount. Adding too much or too little will affect the performance. Therefore, considering the comprehensive performance of the new type of high-strength polymer anchor, the new type of high-strength polymer anchor prepared by the present invention significantly enhances the compatibility and toughness of the material under the condition of simple processing technology; the new type of high-strength polymer anchor not only has excellent high-strength and high-modulus characteristics, but also achieves a significant improvement in stability. The compression molding process is adopted to optimize the mechanical properties and wear resistance of the material, making it more durable and reliable.

[0134] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0135] The present invention and its implementation methods are described above, and such description is not restrictive, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design structures and embodiments similar to the technical solution without creativity, which should all fall within the protection scope of the present invention.

Claims

1. A new type of high-strength polymer anchor, characterized in that: The anchor comprises the following components by weight: FRP matrix: 80-130 parts; Modified ultra-high molecular weight polyethylene: 5-25 parts; Isophthalate: 1-5 parts; Lubricant: 1-4 parts; Coupling agent: 0.5-3 parts.

2. A novel high-strength polymer anchor according to claim 1, characterized in that: The anchor comprises the following components by weight: FRP matrix: 90-120 parts; Modified ultra-high molecular weight polyethylene: 10-20 parts; Isophthalate: 2-4 parts; Lubricant: 2-3 parts; Coupling agent: 1-2 parts.

3. A novel high-strength polymer anchor according to claim 2, characterized in that: The fiberglass matrix is ​​composed of epoxy resin and glass fiber in a weight ratio of 5:

1.

4. A novel high-strength polymer anchor according to claim 3, characterized in that: The lubricant is one of paraffin or stearic acid.

5. A novel high-strength polymer anchor according to claim 4, characterized in that: The coupling agent is silane KH-570.

6. A novel high-strength polymer anchor according to claim 5, characterized in that: The modified ultra-high molecular weight polyethylene comprises the following components by weight: Ultra-high molecular weight polyethylene: 40-50 parts; High-density polyethylene: 30-40 parts; Liquid crystal polymer: 1-10 parts; Polyethylene glycol: 1-2 parts; Cross-linking agent: 1-5 parts.

7. A novel high-strength polymer anchor according to claim 6, characterized in that: The cross-linking agent is 2,5-dimethyl-2,5-di-tert-butylperoxy-3-acetylene.

8. A novel high-strength polymer anchor according to claim 7, characterized in that: The liquid crystal polymer is one of polyaromatic amide liquid crystal polymer and polyaromatic heterocyclic liquid crystal polymer.

9. The method for preparing a novel high-strength polymer anchor according to claim 1, characterized in that: The preparation method comprises: Step 1: preparing a glass fiber reinforced plastic matrix and a modified ultra-high molecular weight polyethylene respectively, wherein ultra-high molecular weight polyethylene, high-density polyethylene and liquid crystal polymer are blended and modified, and polyethylene glycol and a cross-linking agent are added in sequence to obtain the modified ultra-high molecular weight polyethylene; Step 2: chemically reacting the prepared modified ultra-high molecular weight polyethylene with isophthalate; Step 3: fully mixing the product prepared in step 2, the FRP matrix, the lubricant and the coupling agent, and performing compression molding using a compression molding process; Step 4: The formed product is sequentially impregnated, sintered, air-cooled and cut according to a braiding process with a preset number of strands to obtain a new type of high-strength polymer anchor rod.

10. The method for preparing a novel high-strength polymer anchor according to claim 9, characterized in that: The sintering temperature is 200° C.-250° C., and the sintering time is 2-4 hours.